Zero-iodinated contrast retrograde percutaneous coronary interventions of chronic total occlusions using gadolinium and imaging guidance: a case report of a patient with severe anaphylaxis to iodinated contrast. Issue 3 (3rd May 2020) - Gupta, Ankur; Neupane, Saroj; Basir, Mir; Alaswad, Khaldoon
Abstract: Background: Gadolinium-based contrast agents have been used as an alternative to iodinated contrast agents for simple percutaneous coronary interventions (PCIs) in patients with obstructive coronary artery disease. Their use has been limited in complex PCI due to poor image quality with gadolinium contrast. Significant dilution of gadolinium is required in an effort to avoid malignant ventricular arrhythmias. Further, the recommended amount of gadolinium contrast that can be used is very limited. Case summary: We describe a case of patient with severe anaphylaxis to iodinated contrast agents despite pre-exposure prophylaxis with steroids and histamine blockers who underwent intravascular imaging-guided PCI of chronic total occlusions (CTOs) of left anterior descending and dominant left circumflex arteries using gadolinium contrast. Discussion: In patients with anaphylaxis to iodinated contrast agents (i) complex coronary interventions including CTO PCI can be successfully performed without use of iodinated contrast, and (ii) combination of intravascular ultrasound guidance and gadolinium-based contrast agents can be safely and effectively used to perform complex PCI.